Analysis of the Role of Sharia Supervisory Boards - Sri Winarsih; Anggun Okta Fitri; Muhammad Iqbal Fasa (Al-Muamalah: Jurnal Ekonomi Islam, Filantropi dan Perbankan Syariah, 2025)
The role of the Sharia Supervisory Board (SSB) is becoming increasingly important in the development of Islamic banking to ensure that financial institutions operate in accordance with sharia principles. The purpose of this study, Analysis of the Role of the Sharia Supervisory Board in Enhancing Sharia Compliance in Islamic Banking: A Literature Review, is to investigate the strategic role of the SSB in supporting sharia compliance in Islamic banking institutions. Data and information were collected from various academic sources, such as journals, books, and relevant research reports in the last five years. A literature review approach was used as the research method. This study is divided into three main chapters. First, the SSB has a strategic responsibility to supervise and advise Islamic financial institutions to ensure that the principles of Islamic law are applied to all bank goods and services, including avoiding riba, gharar, and maysir. Second, this study found that the SSB faces several problems in carrying out its functions. Some of these problems include the lack of experienced human resources in the field of sharia, the lack of public understanding of the function of the SSB, and pressure from external parties that can hinder the implementation of sharia principles. Third, this study suggests several ways to improve the effectiveness of the SSB. This includes enhancing the capabilities of DPS members through continuous training, increasing collaboration between DPS and relevant authorities such as the National Sharia Board (DSN), and implementing greater transparency of sharia audits.